HAND MOVEMENT METHOD AS AN EFFORT TO IMPROVE MOTIVATION OF MEMORY OF THE QUR'AN ELEMENTARY SCHOOL STUDENTS OF MUHAMMADIYAH KARANGKAJEN YOGYAKARTA INDONESIA - Wasito Wasito; Hanif Cahyo Adi Kistoro (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
This study aims to increase motivation in memorizing the Qur'an by using the hand gesture method on Al-Qur'an material in VA class students at SD Muhammadiyah Karangakjen Yogyakarta. This type of research is Classroom Action Research (CAR). The subjects of this study were 11 students in class VA at SD Muhammadiyah Karangkajen. Data collection techniques using observation, interviews, and oral tests. Data were analyzed qualitatively through reduction, presentation and interpretation of data. Quantitative analysis through descriptive statistical analysis is presented in tabular form. The results showed that there was an increase in students' learning motivation, namely at the action stage 80% of their learning motivation had reached the high category with a score between 25-30. The use of the hand gesture method is known to increase motivation to memorize the Koran in VA class students at SD Muhammadiyah Karangkajen. From this study it can be concluded that there is a significant and positive influence between the use of hand gestures on students' learning motivation in elementary schools.